Antimicrobial activity of essential oils - Murbach Teles Andrade, Bruna Fernanda [UNESP]; Barbosa, Lidiane Nunes [UNESP]; Probst, Isabella da Silva [UNESP]; Fernandes Junior, Ary [UNESP] (Taylor & Francis Inc, 2014)
Natural products have been studied aiming to understand their biological properties. Thus, this study aimed to investigate the antimicrobial activity of twenty-seven essential oils (EOs) used in aromatherapy procedures, a natural therapy with great emphasis currently used against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa strains. The agar dilution method was carried out and minimal inhibitory concentration against 50% and 90% of strains (MIC50% and MIC90% values) were reported. The S.aureus strains were highly susceptible with MIC90% from 0.21mg/mL to black pepper (Piper nigrum) and tea tree (Melaleuca alternifolia) to 26.52mg/mL with copaiba (Copaifera officinalis) EO. Cinnamon (Cinnamomum cassia) and clove (Syzygium aromaticum) EOs were effective against E.coli (2.0mg/mL) while the S.aromaticum EO was against P.aeruginosa (8.29mg/mL). Thus, the higher susceptibility of Gram-positive bacteria when compared with Gram-negative strains was found, and a large variability in the potential antibacterial has also been observed.
Keywords: antibacterial; aromatherapy; EO; minimal inhibitory concentration